PENGARUH PENYULUHAN GIZI SEIMBANG TERHADAP PENGETAHUAN DAN SIKAP REMAJA - Mustikasari Kurnia Pratama, Rini; Yugi Antari, Gladeva; Mustika Handayani, Ayu; Permatasari, Galuh; Sri Yuliastuti, Luh Putu (Jurnal Mutiara Kesehatan Masyarakat, 2022)
Nutritional problems that arise at a young age are triggered by various factors such as poor eating habits, wrong understanding of nutrition, excessive preferences for food types, excessive promotion of food product graphics in the mass media and imported food products. Knowledge of food and nutrition is also one of the factors that influence nutritional status, so formal and non-formal nutrition education is needed. The level of knowledge is very flexible, young people will be positive when choosing the best alternative and tend to do good things. Knowledge is also one of a person's considerations in choosing and consuming food. The purpose of this research is to find out effect of balanced nutrition counseling on Adolescent knowledge and attitudes. This study used a one group pretest-posttest design. Total population of 173 respondents, sampling using probability sampling, namely proportional stratified random sampling, with a total of 63 respondents. Data analysis using t-test. The results of this study found that there was an effect of balanced nutrition counseling on knowledge (p-value 0.000) and attitudes (p-value 0.000) of adolescents. The conclusion that can be drawn from this study is that there is an influence of balanced nutrition counseling coupled with the knowledge and attitudes of adolescents.